Foreign direct investment as a stimulant in productivity convergence process between Visegrad Countries and UE-15 - Wojciechowski, Liwiusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The explanation of reasons and degree of differentiation of wealth between countries remains an important issue in economics today. Theories of economic growth are focused principally on the identification of the long-term determinants of diversification of sources and economic growth, which in turn is associated with the notion of real convergence. Given the supply role of foreign capital that impacts on the economy, in the face of dynamic inflow of foreign direct investment (FDI) into developing countries’ economies, it seems reasonable to include it in convergence process modelling, especially in the modelling of the convergence of productivity. The productivity of the economy is in fact determined by the size of the capital accumulation (both domestic and foreign), savings rate and a number of other conditions. The author hypothesized that the presence of FDI contributes to the acceleration of pace of real convergence between Visegrad countries and EU-15. In this study we estimate interactions between FDI and productivity at both national and NACE level in the years 2000–2014. We concider, in panel data form, among others, productivity in terms of gross value added per employee, degree of penetration of FDI in the economy of the host country. Results suggest conditional β-convergence of productivity existence however they vary across countries, sectors and time. The analysis provides recommendations regarding the arguments for the sectoral policy aimed at encouraging foreign capital to increase its involvement, focusing on reducing productivity gap between the developing and developed countries belonging to European Union.